Identifikasi faktor resiko katarak pada pasien Poli Mata Rumah Sakit Gunung Maria Tomohon - Pitoy, Gisela; Wungouw, Herlina Ineke Surjane; Polii, Hedison (UNIVERSITAS SAM RATULANGI, 2024)
Background: Cataract blindness has become a global health problem and must be solved immediately because blindness can affect the quality of life and productivity. In 2013-2017, a Rapid Assessment of Avoidable Blindness (RAAB) was conducted in 15 provinces in Indonesia, one of which is North Sulawesi. The survey showed that the main cause of visual impairment and blindness in the 15 provinces was untreated cataracts. Aim: To identify the dominant risk factors of cataract patients at the eye clinic of Gunung Maria Hospital Tomohon. Methods: This is descriptive-analytic research with a cross-sectional study design using questionnaires and direct interviews. The research consisted of 40 samples for the inclusion and exclusion. Result: The result showed there were a total of 40 cataract patients, 29 patients aged >60 years (72.5%) and 11 patients aged <60 years (27.5%). According to gender, there were 21 male cataract patients (52.5%) and 19 female cataract patients (47.5%). Based on smoking history, 17 patients smoked (42.5%) and 23 patients who did not smoke (57.5%). Based on the duration of sun exposure, 12 patients were daily exposed to sunlight for <5 hours (30%) and 28 patients were daily exposed to sunlight for >5 hours (70.0%). Based on the history of lens trauma, seven patients had a history of lens trauma (17.5%), and 33 patients did not have a history of lens trauma (82.5%). Conclusion: The dominant risk factors for cataract patients in the eye clinic of The Gunung Maria Hospital Tomohon are the age factors >60 years and patients who were exposed to sunlight for >5 hours daily. Keywords: cataract, risk factors